2023
DOI: 10.3389/fpubh.2023.1180914
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with falls among hospitalized and community-dwelling older adults: the APPCARE study

Abstract: BackgroundFalls are a leading cause of disability. Previous studies have identified various risk factors for falls. However, contemporary novel research is needed to explore these and other factors associated with falls among a diverse older adult population. This study aims to identify the factors associated with falls among hospitalized and community-dwelling older adults.MethodsCross-sectional data from the ‘Appropriate care paths for frail elderly people: a comprehensive model’ (APPCARE) study were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…It was found that women had an increased risk of experiencing falls compared to men, which aligned with the conclusions drawn in previous studies ( 18 , 32 , 34 ). In addition, significant factors inversely associated with falls include: advanced age, mild to moderate of disability, and ranging from acceptable to poor sleep quality.…”
Section: Discussionsupporting
confidence: 90%
“…It was found that women had an increased risk of experiencing falls compared to men, which aligned with the conclusions drawn in previous studies ( 18 , 32 , 34 ). In addition, significant factors inversely associated with falls include: advanced age, mild to moderate of disability, and ranging from acceptable to poor sleep quality.…”
Section: Discussionsupporting
confidence: 90%
“…These conditions could be managed adequately by care providers. Our study cohort was older residents in a long-term facility who reported insignificant factors for falls, including level of education [6], length of residency [27], depression [2], and past fall experience [24,27].…”
Section: Discussionmentioning
confidence: 99%
“…[80][81][82] Moreover, in addition to prioritizing fall prevention within healthcare organizations, future research endeavors could concentrate on extending fall prevention initiatives to the community level. 83,84 Implementing measures such as public education and the establishment of community support networks can effectively enhance fall awareness and prevention among older adults residing in the community. Furthermore, aggressive treatment of CKD-related complications, such as arthritis and neurological disorders, can help reduce falls.…”
Section: Othersmentioning
confidence: 99%